Analisis Yuridis terhadap Penegakan Hukum Alih Fungsi Ruang Terbuka Hijau di Kawasan Perkotaan - Ahmad Dzaki; Daffa Amanullah; Muhamad Syahrul Maulana; Irfan Maulana (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This study examines the issue of law enforcement related to the conversion of Green Open Spaces (GOS) in urban areas. Using a normative juridical research method with legislative and conceptual approaches, this research analyzes the implementation of Law No. 26 of 2007 on Spatial Planning, which mandates the availability of GOS at a minimum of 30% of the total urban area. The findings indicate that law enforcement in GOS conversion faces multiple challenges, including inconsistent regulatory implementation, budget constraints, weak inter-agency coordination, and obstacles in monitoring and enforcement. The pressures of urban facility development and population growth due to urbanization further complicate efforts to preserve GOS. Optimizing the role of local governments in GOS protection and management is carried out through the implementation of the Spatial and Regional Planning involving various related agencies. The Ministry of Environment’s Adipura Program also plays a role in promoting enhanced environmental management performance by adhering to eight essential criteria within legal products related to environmental and ecosystem protection. This study recommends strengthening the GOS management system through improved inter-agency coordination, adequate budget provision, and the consistent application of firm sanctions.